Lean principles adoption in environmental management system (EMS): A survey on ISO 14001 certified companies in Malaysia - A. P., Puvanasvaran; M. R., Muhamad (Omnia Science, 2012)
Purpose: The purpose of this study is to examine the characteristic of the lean principles in ISO 14001 and to propose linkage between lean principles and ISO 14001. Design/methodology/approach: To achieve the objective of the study, literature survey and quantitative research method using questionnaire survey are used. Findings and Originality/value: The findings of this study confirm that ISO 14001 certified company adopted lean production practices. The study also proves that lean principles have a positive and significant relationship with ISO 14001 EMS and the linkage can be made between lean principles and ISO 14001 to achieve Continual Improvement. Research limitations/implications: The small sample sizes of the participating companies are the main limitations of this study and this research mainly focus on the manufacturing environment and services industry in Malaysia. Practical implications: This research shows that all ISO 14001 companies do adopt at least one of lean production practices and the main findings are lean principles has positive and highly significant relationship with ISO 14001 requirements. This is because the integration of lean principles in ISO 14001 will serve practical methods for ISO14001 EMS to achieve the continual improvement.